Strategi Tim Produksi Audio Series Catatan Pembalasan Fajar Dalam Mempertahankan Pendengar Aplikasi Noice - Sativa Putra Prasetyo; Indah Suryawati; Rocky Prasetyo Jati; Eko Sumardi (PROPAGANDA, 2023)
This research aims to determine the production team's strategies for maintaining listeners of the audio series "Catatan Pembalasan Fajar" on the Noice application. The research method used is qualitative descriptive with data collection techniques such as interviews, observations, and documentation. The paradigm employed in this research is post-positivism. The subjects of this study are the production team of the "Catatan Pembalasan Fajar" audio series on the Noice application, including the producer (key informant) and audio engineer (informant). The object of this research is the "Catatan Pembalasan Fajar" audio series on the Noice application. After conducting the research using the program strategy proposed by Peter Pringle, which includes program planning, program production, program execution, program supervision, and program evaluation, the researcher found that the production team implemented several strategies to retain listeners of the "Catatan Pembalasan Fajar" audio series on the Noice application. These strategies include selecting the thriller genre due to high demand from listeners, using bold and assertive sound design, creating an engaging storyline, and paying attention to interactions and listener interests through the comment section of each episode. Despite facing production challenges, the production team successfully created a program that attracted listeners' interest and provided a satisfying audio experience.